The Impact of diabetes on long-term prognosis in non-ST elevation acute coronary syndrome - Farouk BOUKERCHE; Leila HAMMOU; Nadia LAREDJ (Journal de la Faculté de Médecine d'Oran)
Abstract Background-In Algeria, there is a lack of up-to-date information regarding the burden of diabetes in patients with coronary disease and its long-term prognostic impact. Our objective was to evaluate the long-term prognostic impact of diabetes in the context of contemporary management of patients with non-ST elevation acute coronary syndrome including a systematic interventional approach. Methods - A prospective study including all patients admitted to the cardiology department of CHU Oran for non-ST elevation ACS from November 2015 to October 2016 and with a five-year follow-up, a comparative study was carried out between the known diabetic group and the non-diabetic group in terms of occurrence of major adverse cardiovascular and cerebrovascular events. Results -Of the 296 patients initially included, 274 completed the 5-year follow-up (7.4% lost at follow-up). The diabetic group included 128 patients (46.7%) and is differentiated from the non-diabetic group by the female predominance, more hypertension, dyslipidemia, and obese and fewer smokers, more three-vessel disease, therapeutically more frequent use of coronary artery bypass grafting. On the prognostic level, there is no significant difference in cardiovascular mortality (19.5% vs. 12.3%; p=0.134). On the other hand, there were more major adverse cardiovascular and cerebrovascular events in diabetics (43.0% vs 27.4%; p=0.008). In multivariate analysis, diabetes was an independent risk marker for the occurrence of major adverse cardiovascular and cerebrovascular events at 5 years, and cardiovascular mortality at 5 years, it is diabetes with more than 10 years old and not diabetes in general which, is a prognostic marker. Conclusion - With contemporary management of non-ST elevation ACS, the prognostic weight of diabetes persists but tends to decrease.